Development of E-Portable Book Media as an Innovation in Religious Activities of the Religious Study Group - Triani, Iit; Pasaribu, Fatima Putri (South Sulawesi Education Development (SSED), 2025)
This research aims to develop an E-Portable Book as a supporting medium for religious activities in the religious study group. Development is carried out using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, and pilgrims of the religious study group. Data is collected through validation sheets and practical questionnaires. The validation results showed an average score of 88.33% (Very Valid), while the practicality test obtained an average score of 86.67% (Very Practical). This media is considered easy to use, making it easier for pilgrims to access the material and increasing involvement in the study. The interpretation of the results shows that the E Portable Book is a feasible and effective alternative to community-based religious learning media. These findings are expected to encourage the use of digital technology in non-formal education, thereby expanding access to and improving the quality of learning.